PENGEMBANGAN MODUL AJAR BERBASIS PEMBELAJARAN BERDIFERENSIASI DENGAN PENDEKATAN PROJECT BASED LEARNING (PjBL) TOPIK CAHAYA DAN SIFATNYA UNTUK SISWA KELAS V SD NEGERI 92 PALEMBANG - Wahyu Pratama; Henni Riyanti; Patricia H. M. Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This reseacrh aims to develop a teaching module based on differentiated learning with a Project Based Learning (PjBL) approach on the material "Light and Its Properties" for grade V students of SD Negeri 92 Palembang which is valid, practical and effective. The development model used is ADDIE, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include interviews, documentation, questionnaires and tests. Interviews and documentation are used at the needs analysis stage, while questionnaires are used to measure the level of practicality of the module, and tests are used to assess effectiveness based on learning outcomes. Data analysis techniques include module validity analysis carried out by three experts, namely material, media, and language experts. The results of the validity analysis show that the module is classified as very valid with an average of 85.7%. The practicality analysis of the module was tested through individual trials, small groups, and field tests which obtained an average of 82.18% with a very practical category. The analysis of the effectiveness of the module is proven through the increase in student learning outcomes between the pretest and posttest, with most students showing an increase in the high category based on the N-Gain analysis with an average of 85.6% in the very effective category. The results of the study concluded that the developed teaching module is valid, practical, and effective to be applied in science learning and supports the implementation of the Independent Curriculum through a student-centered approach and learning differentiation.